SKRINING DAN UJI POTENSI ENTOMOPATOGEN LOKAL (Bacillus sp.) DARI LARVA Aedes aegypti - Hakimatul Husniyah (PT Innovative Academic Journals, 2025)
This research aims to isolate local entomopathogenic bacteria Bacillus sp. from the body of Aedes aegypti larvae and to know the potency of local entomopathogenic bacteria Bacillus sp. in killing Aedes aegypti III instar larvae. This research is descriptive study with qualitative and quantitative approaches. Bacillus sp. was isolated by destroying the larvae sample and heated in a temperature of 70ºC. Then, the sample was diluted 10-1–10-3. After that, each dilution was grown for 48 hours. Then, purification of bacteria suspected as Bacillus was performed. Gram staining and spore staining as microscopic tests were carried out on colonies that resembled Bacillus sp.. Bacillus sp isolate which have been obtained was used in preliminary and advanced stages of potential test against instar larvae III of Aedes aegypti. Data was visualized in tables and graphs, then analyzed descriptively. The results of the study showed that in the preliminary stage of potential test, 120 isolates of Bacillus sp. were obtained, as many as 32% had no potency, 41% had low potency, 15% had moderate potency, and 12% had high potency. The results of the advanced stage of potential tests on high-potential isolates showed 3 isolates with the highest potency in killing Aedes aegypti larvae. They were SB3 3, SB9 1, and SD4 2 with percentage of larval mortality of 100%, 96.7%, and 100%, respectively.